Suicide Prevention A Practical Guide for the Practitioner (Springer International Publishing, 2018)
The book begins by establishing the neurobiology of suicide before discussing the populations at risk for suicide and the various environments where they may present. The book addresses the epidemiology, including groups at heightened risk; etiology, including several types of risk factors; prevention, including large-scale community-based activities; and postvention, including the few evidence-based approaches that are currently available. Unlike any other text on the market, this book does not simply focus on one particular demographic; rather, the book covers a wide range of populations and concerns, including suicide in youths, racial minorities, patients suffering from serious mental and physical illnesses, psychopharmacological treatment in special populations, and a wide array of challenging scenarios that are often not addressed in the very few up-to-date resources available. Suicide Prevention is an outstanding resource for psychiatrists, psychologists, hospitalists, primary care doctors, nurses, social workers, and all medical professionals who may interface with suicidal patients.